1995
DOI: 10.1111/j.1432-1033.1995.tb20208.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Haem Electronic Structure in His-Met Cytochromes c by 13C-NMR. The Effect of the Axial Ligands

Abstract: The assignment of 13C resonances of nuclei alpha to the haem in horse ferricytochrome c is completed and the Fermi contact shifts are evaluated at 30 degrees C and 50 degrees C using empirical magnetic susceptibility tensors to correct for dipolar interactions. The Fermi contact shifts are fitted to a model of molecular orbitals of eg symmetry, which are subject to a rhombic perturbation. A similar analysis is performed using published data for Pseudomonas aeruginosa cytochrome c551. The relationship between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
109
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 34 publications
8
109
1
Order By: Relevance
“…Average values of chemical shifts measured in several cytochromes were used as diamagnetic reference [23] and the hyperfine coupling constant was fixed at À36 MHz [17]. The fitting was performed using the Nelder-Mead Simplex algorithm implemented in MATLAB.…”
Section: Determination Of the Axial Ligand Geometrymentioning
confidence: 99%
“…Average values of chemical shifts measured in several cytochromes were used as diamagnetic reference [23] and the hyperfine coupling constant was fixed at À36 MHz [17]. The fitting was performed using the Nelder-Mead Simplex algorithm implemented in MATLAB.…”
Section: Determination Of the Axial Ligand Geometrymentioning
confidence: 99%
“…The strength of the axial imidazole coordination contributes to the complex pattern of factors controlling the activity of these proteins [2,3]. The axial binding strength can generally be modulated through three main mechanisms: (1) the hydrogen-bonding interaction between the imidazole and a nearby carboxylate group [4]; (2) a change in the orientation of the imidazole plane [5,6]; and (3) the introduction of a conformational strain as a consequence of the binding of the proximal residue, producing some tilting of the imidazole group [7].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies of ferricytochroine c3 from DvH, the "C resonances of the haem substituents were also identified . These assignments formed the basis for the elaboration of a theoretical model which describes the Fermi contact shifts of those carbon nuclei in terms of a molecular orbital of eg symmetry with a rhombic perturbation (Turner, 1993(Turner, , 1995Turner et al, 1995). Moreover, the study has shown that the Fermi contact shifts are directly related to the orientations of both axial ligands and hence that the axial ligands dominate the rhombic perturbation.…”
mentioning
confidence: 99%
“…These shifts may be scalar (Fermi contact shift) or dipolar (pseudocontact shift) in origin. The first type is restricted to the haem moieties and their ligands and contains information about the distribution of the unpaired electron and thus about the haem electronic structure (Shulman et al, 1971;Keller et al, 1976;Turner, 1995), whereas the second type depends on precise geometrical functions, thus providing important structural information (Barry et al, 1971 ;Xavier et al, 1993).…”
mentioning
confidence: 99%